The effects of calcium, magnesium and citrate health supplements on urinary risk factors for calcium oxalate kidney stone formation - Allie-Hamdulay, Shameez (Department of Chemistry, 2024)
[Pages missing] This thesis was undertaken to investigate the effects of various health supplements on the risk of calcium oxalate (CaOx) kidney stone formation. Four separate studies comprised the entire project. In the first study, a new approach was implemented to investigate the individual, additive and synergistic effects of calcium, magnesium and citrate health supplements on the urinary risk factors for CaOx kidney stone formation in eight healthy males. · While previous studies have examined the effects of individual preparations, few (if any) have addressed the issue of chemical interactions or synergism between different agents. The experimental design which was employed was a "Complete Latin Square Design" in which each subject was allocated to a randomized sequence of seven supplemental protocols in addition to the normal diet. These protocols comprised of calcium, magnesium and citrate supplements and combinations thereof. Supplementation lasted for 1 week. 24-hour urines were collected at baseline and during the final day of each supplemental protocol. The urine composition, relative supersaturation (RS), Tiselius risk index, metastable limit (MSL) and particle volume-size distributions were measured for each urine sample. The results showed that the activity of citrate-containing protocols in reducing several physicochemical risk factors for CaOx stone formation was superior to those containing calcium or magnesium alone and also that it behaves this way irrespective of whether the latter two components are present or not. The study also identified three interactions, viz. magnesium enhances citrate's ability to lower RS brushite (favourable synergistic interaction) and attenuates its ability to raise urinary pH (unfavourable synergistic interaction) and finally, calcium enhances citrate's ability to lower RS uric acid (additive effect). In the second study, the potential prophylactic and therapeutic properties of a South African product (CitroSoda: sodium citrate bicarbonate tartrate), previously untested in the management of CaOx urolithiasis, was investigated. 30 healthy males (MC), 30 male CaOx stone formers (MSF), 30 healthy females (FC) and 30 female CaOx stone formers (FSF) participated in the study. The experimental design which was implemented was a placebo controlled, randomized, "within-patient" design. All the subjects were required to provide two 24h urine collections prior to the commencement of the trial which were used as baseline samples. Twenty subjects in each group ingested CitroSoda and ten subjects V ~•~=•w~,-~,~~==w in each group ingested a blinded placebo. Supplementation lasted for 7 days. In addition to the baseline 24h urine samples, subjects provided 24h collections on day 7 (final day of supplementation) and on day 10 (3 days after supplementation was suspended). The urine composition, relative supersaturation (RS), Tiselius risk index, metastable limit (MSL), particle volume-size distribution and [ 14C]-oxalate deposition were measured for each urine sample. Scanning electron microscopy was also performed on selected samples. The results showed that CitroSoda favourably altered four biochemical risk factors in all four groups: pH and citrate excretion increased and the RS of uric acid and the RS of CaOx decreased. No unfavourable changes occurred in any of the risk factors. These results demonstrated that CitroSoda has the potential to be an effective preparation for the prophylactic and therapeutic management of CaOx urolithiasis. Since the question of whether there is a stone forming risk associated with the ingestion of calcium supplements with meals or between meals remains unanswered, the third study was undertaken under strictly controlled conditions, to investigate urinary oxalate excretion as a function of the time at which a calcium supplement is ingested relative to an oxalate-rich meal. 20 healthy males participated in the study in which six different protocols were investigated over a six-hour time period. Subjects provided a fasting overnight urine sample on the morning of trial and thereafter ingested a standardized oxalate-rich meal. In the first protocol no calcium supplement was administered; in the 2nd protocol the calcium supplement was given with the meal and in the 3rd , 4th , 5th and 6th protocol, the supplement was given 1 hr, 2hrs, 3hrs and 4hrs respectively after the meal. Subjects were required to provide urine samples at hourly intervals throughout the protocol, after which the urine composition and ion activity product of calcium oxalate (AP(CaOx) index) for each sample was calculated. The study demonstrated that calcium supplements taken 1 hour after an oxalate-rich meal produced the lowest total oxalate excretion over the 6-hour period following the ingestion of the oxalate-rich meal, relative to other protocols. The urinary calcium excretion was fairly steady in this protocol whereas for the other protocols, a dramatic surge was observed at some stage during the 6 hour test period. The AP(CaOx) index values supported the choice of this protocol as the optimum one because it displayed a level trend which was relatively lower (or equal) to that of the other protocols. In the final study, a speciation program (JESS) which is not well-known in urolithiasis research, was firstly used to compare RS outputs with those of the more familiar EQUIL2.